PENGARUH PENGAJARAN FIRMAN TUHAN TENTANG KESUKSESAN MENURUT KITAB 2 TAWARIKH 20:1-32 TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS VIII SMP KRISTEN GRACI KLATEN. - Dekiman Morip; LIe Agan (Universitas Kristen Immanuel, 2022)
The title of this thesis is: The Effect of Teaching God's Word on Success according to the Book of 2 Chronicles 20:1-32 on the Character Building of the VIII th Graders of Gracia Christian Middle School, Klaten. Example is the basis of learning activities and when a Master in Jehoshaphat strengthens the area. God also blessed king Jehoshaphat. Jehoshaphat was a man who sought God through prayer, so God heard his prayer and saved him. From the enemy's attack using it, I am committed to worship as Jehoshaphat re-established true worship. The teacher has reduced the effectiveness of learning. So this role must be understood so that it can enrich the meaning of learning. Abstract is a brief description of the whole article or scientific paper, the contents of which contain four components, namely: (1) Problems and objectives; (2) the method used; (3) Results and Discussion; and (4) Conclusions and Suggestions. written in two languages, namely Indonesian and English. In addition, the abstract is written in one paragraph without footnotes or bibliography, one space, and contains a maximum of 250 words in Indonesian.